2015
DOI: 10.1186/s40709-015-0026-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the microbiological quality of fresh produce on sale in Sicily, Italy: preliminary results

Abstract: BackgroundFresh produce occupies an increasingly important place in the human food supply because of its health-promoting nutritional properties. Most fresh produce is eaten raw or after minimal processing and, consequently, pathogen contamination can represent a serious health risk. There has been an increase in foodborne outbreaks and cases associated with fresh produce, but literature data about the prevalence of pathogen contamination are inconsistent. This study was undertaken to assess the hygienic quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 24 publications
5
42
2
Order By: Relevance
“…Johnston et al () detected low levels of E. coli and coliforms on fresh produce. Similar to other findings (Cardamone, Aleo, Mammina, Oliveri, & Di Noto, ), coliforms and E . coli were detected at concentrations complying with current national (DWAF, ) and FAO () regulations in market ready lettuce and baby spinach respectively.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Johnston et al () detected low levels of E. coli and coliforms on fresh produce. Similar to other findings (Cardamone, Aleo, Mammina, Oliveri, & Di Noto, ), coliforms and E . coli were detected at concentrations complying with current national (DWAF, ) and FAO () regulations in market ready lettuce and baby spinach respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Contaminated irrigation water is one of the factors influencing microbiological quality of leafy green vegetables (Seow, Agoston, Phua, & Yuk, 2012). Our study reports E. coli levels of 18, 20, and 27% for baby spinach, lettuce and cabbage, respectively; this is higher than concentrations previously reported by Cardamone et al (2015). Traditionally coliforms were used as indicators of fecal contamination and potential presence of pathogenic bacteria (Steele & Odumeru, 2004), hence they were tested for in this study.…”
Section: Discussionsmentioning
confidence: 70%
“…Recent years have witnessed an increase in the frequency of occurrence of these infections. Studies in developed and developing countries have demonstrated the potential of raw vegetables to transmit pathogens [8, 9, 21–23]. Data on microbial quality of vegetables in Cameroon is scarce despite the fact that it has witnessed an increase in vegetable consumption and cultivation, as cultivation in addition to ensuring food security, has become an income generating activity [17, 24].…”
Section: Introductionmentioning
confidence: 99%
“…Microbiological qualities and prevalence of pathogens in fresh produce can vary significantly due to different major factors that can affect microbial safety. Such factors include the location of samples, growth conditions, harvesting season and method, and the microbiological analysis method used (Cardamone and others ). Such variations highlight the difficulties in identifying the risk, the sources of contamination, and control strategies (FAO/WHO ).…”
Section: Introductionmentioning
confidence: 99%